Expression of GM2 Activator Protein as a Potential Biomarker for Lung Cancer - Laddawan Potprommanee (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Lung cancer is a leading cause of cancer–related deaths worldwide. Finding effective biomarkers for early diagnosis would be useful for potential cure of this deadly disease. In previous report, the protein expression pattern of urine samples from lung cancer patients and healthy controls were compared using two-dimensional gel electrophoresis (2-DE). Intensity of GM2 activator protein (GM2AP) in lung cancer patients was found with 2.5-4.0 fold higher than that found in healthy controls. Hence, GM2AP became the protein of interest. This protein was focused because it was related to tumor-associated gangliosides found in cancer progression. The aim of this study was to investigate and validate the potential of GM2AP as a biomarker for diagnosis of lung cancer. First, proteomic approach was employed to confirm the increased levels of GM2AP in urine samples from lung cancer patients and healthy controls. The result revealed that GM2AP levels in subtypes of lung cancer patients were greatly over-expressed when compared with the mean of healthy controls, consistent with the increase in protein spot intensity observed in the 2-DE gels. The expression levels of GM2AP in urine were subsequently detected by Western blot analysis and quantified using ELISA. The present study also showed significantly higher urinary GM2AP level in patients (n= 48) compared to healthy controls (n = 44). However, the results remained unclear because the urine samples were from lung cancer patients, who had received anticancer treatments, and the amounts of urine samples from lung cancer patients were limited. Therefore, we have further confirmed the expression of GM2AP level in a large group of lung cancer patients using urine (n =133) and serum (n = 133) specimens, who have not received anticancer treatments. Levels of GM2AP were 8.11 ± 1.36 fold increases in urine and 5.41 ± 0.73 fold increases in serum of lung cancer patients when compared to those in healthy controls (P < 0.0001). The urinary GM2AP possessed an area under curve (AUC) value at 0.89 with sensitivity of 88.46% and a specificity of 85.71%. The serum GM2AP showed an AUC value at 0.90 with sensitivity of 100% and a specificity of 82.7%. Therefore, the expression of GM2AP in urine or serum has high accuracy as a diagnostic marker for lung cancer. Levels of GM2AP in urine and serum of lung cancer patients were significantly correlated with pathology stage (urine, P = 0.009; serum, P < 0.001). Using immunohistochemistry, the expression of GM2AP was found at 83.9% (122/143) of non- small cell lung cancer (NSCLC) patients and absence in normal tissue. The GM2AP expression was significantly correlated with pathology stage (P = 0.0001). Patients with higher GM2AP expression had shorter overall survival (P = 0.045) and disease-free survival (P = 0.049) than those with lower GM2AP expression, as assessed by the Kaplan-Meier method. Moreover, the multivariate analysis revealed that the stage (hazard ratio 0.335 [95% CI, 0.163-0.689]; P = 0.003) and the GM2AP score (hazard ratio 0.475 [95% CI, 0.250-0.906]; P = 0.024) were significant independent predictors of the disease free-survival. Stage (hazard ratio 0.364 [95% CI, 0.216-0.612]; P < 0.001) and the score (hazard ratio 0.563 [95% CI, 0.349-0.910]; P = 0.019) were also significant independent predictors for overall survival. In addition, NanoLC-MS/MS provided evidence of an increase of GM2AP with the glycan structure identification from doublely charged ion at m/z 1202.1025 corresponding to the structure of (Hex)3(HexNAc)2(Fuc)1 linked with peptide (PIIVPGNVTLSVVG). All data supported that GM2AP level in urine and serum can be useful diagnostic and prognostic biomarker for lung cancer.